2022
DOI: 10.1007/s15010-022-01789-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the interferon-gamma release assay in acquired immunodeficiency syndrome patients with suspected tuberculosis infection: a meta-analysis

Abstract: Purpose The diagnostic accuracy of the interferon-gamma release assay (IGRA) in immunosuppressed patients remains unclear. Methods A systematic review and meta-analysis were performed for diagnostic test accuracy of IGRA in tuberculosis (TB) infection among people living with HIV (PLWHIV). Summary estimates of sensitivity and specificity were calculated using both univariate and bivariate models. Results The meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Consistent with the literature [ 17 ], tuberculosis combined with HIV infection is associated with false-negative IGRA results, which may be due to the loss or dysfunction of the MTB-specific T-cell memory response in HIV patients [ 18 ]. Decreased lymphocyte number or abnormal lymphocyte function in patients with connective tissue disease are the main risk factors leading to negative results of the interferon-γ release test [ 19 ], which can also explain our study results.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with the literature [ 17 ], tuberculosis combined with HIV infection is associated with false-negative IGRA results, which may be due to the loss or dysfunction of the MTB-specific T-cell memory response in HIV patients [ 18 ]. Decreased lymphocyte number or abnormal lymphocyte function in patients with connective tissue disease are the main risk factors leading to negative results of the interferon-γ release test [ 19 ], which can also explain our study results.…”
Section: Discussionsupporting
confidence: 82%
“…The IGRA is a method to detect latent TB infection. 16 However, this is not a useful tool for confirming the diagnosis because only 40% of participants in our study had a positive IGRA.…”
Section: Discussionmentioning
confidence: 61%
“…Our finding of a higher magnitude of IL17-than IFNγ-producing CD4 + T cells in HIV-ART upon Mtb300 stimulation is contrary to the impression that IFNγ production is the dominant response to Mtb infection [41]. This may have implications for TB diagnosis since current tests for detection of responses to Mtb antigens rely on IFNγ production, whose sensitivity is variable and is impacted by HIV infection [42]. Recent studies revealed evidence that people who have been exposed to Mtb but remain negative by IFNγ responses have detectable responses to Mtb antigens when other readouts are used [43].…”
Section: Discussionmentioning
confidence: 77%